Effectiveness of Mindfulness-Based Cognitive Therapy on Mental Pain, Distress Tolerance and Psychological Hardiness in Breast Cancer Patients - Seyed Alitabar, Seyed Hadi; Zadhasn, Zohreh (Health Nexus, 2023)
The aim of this study was to determine the effectiveness of mindfulness therapy on mental pain, distress tolerance and psychological hardiness in breast cancer patients. The method of this study was quasi-experimental with pretest-posttest design and a one-month follow-up with control group. The statistical population consisted of all female patients referred to the medical clinics of Babol in 2022 who received definite diagnosis of breast cancer. Among these, 30 patients with breast cancer were selected by non-random sampling method and were randomly assigned to two experimental groups (mindfulness therapy) and control group (15 patients in each group). Mindfulness therapy was performed in 8 sessions of 90 minutes in the experimental group. Data were collected using Psychological Hardiness Questionnaire (2003), Distress Tolerance Scale (2005) and Mental Pain Inventory (2003). Data were analyzed using SPSS-22 software and repeated measure analysis of variance. The results showed that mindfulness therapy is effective on mental pain, distress tolerance and psychological hardiness in patients with breast cancer. It can be concluded that mindfulness therapy is effective on subjective pain, distress tolerance and psychological hardiness in patients with breast cancer and can be used to reduce the adverse effects of the disease on patients’ lives and to take supportive measures